Variation of the fine-structure constant: An update of statistical analyses with recent data - Kraiselburd, L. (2013)
Aims. We analyze the consistency of different astronomical data of the variation in the fine-structure constant obtained with Keck and VLT. Methods. We tested the consistency using the Student test and confidence intervals. We splited the data sets into smaller intervals and grouped them according to redshift and angular position. Another statistical analysis is proposed that considers phenomenological models for the variation in α. Results. Results show consistency for the reduced intervals for each pair of data sets and suggests that the variation in α is significant at higher redshifts. Conclusions. Even though the dipole model seems to be the most accurate phenomenological model, the statistical analyses indicate that the variation in α might be depending on both redshift and angular position. © 2013 ESO.